Distribution of transient overvoltage in wind turbine systems under direct lightning strikes - Ahmed, Rebaz Jamal (2014)
Wind turbines are tall structures, and the reflections of a direct lightning at various interfaces have a significant effect on the voltage distribution; hence they should be taken into account in the computation models. Thus, this thesis contains a brief introduction to lightning, lightning discharge process and the consequences of a direct lightning strike to an elevated structure (such as a wind turbine), an analysis on the effects of overvoltage produced by electromagnetic environment, and the effects of the reflections. All parts related to the power generation in a wind turbine, including step up transformers are modeled by lumped parameters using the Matlab/Simulink software. The transient response is obtained by applying the lightning impulse current to the equivalent circuit under several values of the grounding resistance (i.e. 1 ohm, 10 ohm and 20 ohm) and several cable sheath grounding methods with different lightning strike waveforms. For the channel base lightning representation, many current functions were considered in the past. Some of these functions were found to have problems related to their discontinuities or the discontinuities of their derivatives at the onset. Such problems appear in the double exponential function and its modifications. However,these problems have been solved in Heidler functions, where they are used and modeled for the purpose of this study. The main contribution of the thesis is that; real lightning current source parameters have been used for the lightning current source which in the other studies only standard parameters is used and they donot resemble the direct lightning current, and this causes underestimation of the results. The results show that the location of the cable shield grounding, the lightning current type and the grounding resistance values have significant influence on the produced overvoltage at the input and output of transformer terminals. For instance if the cable shield is grounded from both the top and the bottom ends of the transformer, the lowest overvoltage is obtained on the transformer terminals Also, appropriate surge protection devices are designed to reduce harmful effects due to dangerous overvoltage impulses. And it’s shown that with these surge arresters the overvoltage values are lowered to a safe level.